The effects of emotions on the disposition to normative and non-normative political action in the context of the Chilean post-social outburst - Hatibovic, Fuad; Sandoval, Juan; Faúndez, Ximena; Gaete, Jose-Manuel; Bobowik, Magdalena; Ilabaca, Paola (Frontiers in Psychology, 2023)
This article analyzes the role of Chileans' emotions as predictors of normative and non-normative politi-cal action in the context of the post-social outbreak and the constituent process. We carried out three descriptive studies: first, a study conducted one year after the social outburst (n = 607); a second one carried out before the constitutional referendum (n = 320); and a third study conducted after the consti-tutional referendum (n = 210). The results indicated that participants present a higher disposition to normative over non-normative political action, although both lose strength as the studies temporally move away from the social outburst. Also, our research established that emotions directed towards dif-ferent events related to the Chilean political process play a conspicuous role in predicting the disposition to mobilize in a normative and non-normative way.